Novel Improves Student English Skills - Rany Raissa Palupi; Arina Shofiya; Erna Iftanti (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2021)
English novels can be one of the teaching materials because English novel is an authentic media for learning media. Student can improve their English skill using English novel because English novel has the element that can help student learning English such as; vocabulary, grammar, socio-culture.In this article, the researcher wants to know if the English novel can help student improving their English ability or not. The reason why the researcher conducts this research is that the researcher found the phenomenon about it. In nowadays era, especially during covid 19 eras, student habit in learning is changing. Some students started to learn English using English online novels because an online novel is easy to access. Because of this phenomena, the researcher wants to know if student ability increases or not while they used English online novels to learn English.      In this article, the researcher used a qualitative research design to conduct the research. The research has 10 samples that have different backgrounds of the school. The researcher interviews the subject through Facebook because it is the easy way to conduct the interview. The result of this research is, student ability is increases while they used English online novels to learn English. But even though their ability is increase, there are several aspects must be improved, such as they need practice their ability not only in writing but also in speaking, they need read English novel continuously to maintain their ability in English.